The relationship between carotid intima-media thickness, serum biomarkers of cardiovascular disease, and HIV-infection in a South African study population - Sana, Charania (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.